APPLYING THE DIALOGUE METHOD IN TEACHING THE ARABIC LANGUAGE AT SMAIT AL-ARABIYAH: تطبيق طريقة الحوار في تعليم اللغة العربية - Salam, Adnin A.; Safaini, Safaini (Institut Agama Islam Negeri Lhokseumawe, 2024)
The Dialogue method is considered one of the most effective ways to teach Arabic, as it helps students achieve fluency in pronunciation and sentence construction. Hence, the researchers aim to implement this method in their Arabic teaching due to the struggle of students at SMAIT Al-Arabiyah with sentence construction. The research questions are: What is the process of learning Arabic using the Dialogue method at SMAIT Al-Arabiyah, and how effective is learning Arabic using the this method? The objectives of the research are to identify the process of learning Arabic through the Dialogue method at SMAIT Al-Arabiyah and to assess its effectiveness. Researchers hypothesize that the Dialogue method effectively enhances Arabic conversation skills. They employed experimental research methods and found that the application of the Dialogue method involved four sessions: an initial meeting for method explanation and pre-test, two sessions for method application, and a final session for post-test. The results showed that the method is effective, with an average pre-test score of 67.60 and a post-test score of 72.39, and a T score of 3.57. These findings indicate that this method is highly suitable for improving students' speaking abilities.